New Insights into the Anion Transport Selectivity and Mechanism of Tren‐based Tris‐(thio)ureas. Issue 41 (19th June 2018) - Jowett, Laura A.; Howe, Ethan N. W.; Wu, Xin; Busschaert, Nathalie; Gale, Philip A.
Abstract: The anion transport properties of a series of previously reported tren‐based anionophores have been revisited using new assays designed to measure anion uniport. This study provides new insights into the transport mechanism and selectivity of this important class of transporters. Specifically, we report the chloride and nitrate transport selectivity of these systems and quantify sulfate transport to determine EC50 values for sulfate transport for the first time. Two new assays were developed to study bicarbonate transport allowing accurate quantification of chloride/bicarbonate exchange. Abstract : Old but new : A series of previously reported tris‐(thio)ureas have been tested in a variety of anion uniport assays allowing anion selectivity to be determined.